PENGARUH SUGESTI DALAM PENCAPAIAN PRESTASI BELAJAR SISWA - Trinurmi, Sitti (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2014)
Suggestion is very important in the learning achievements of students, because the suggestion will be easily accepted by others. When the critical power is inhibited, it would be easily accepted others, when his ability was dissociation. Suggestions will be easily accepted others, when the material has the support of many people (majority of suggestion), the giver of suggestion is the one who has the authority and, if the person concerned has no opinion that precedes the line. How do suggestion for students in learning achievement is; an educator should instill a strong intention and motivation in the students themselves, identifies the position, gestures, language as well as brain waves with learners. Educators must combine between equate positions and directing something, using language or positive words, give sincere compliments to learners, especially when he managed to do or accomplish achievements, and provide a role model through speech and behavior consistent